Mapeando a geografia escolar : identidades, saberes e práticas - Borges, Vilmar José (2001)
This survey goals a reflection about knowledges and pedagogical practice of Geography teachers, whose act in the final grades of the public Fundamental School in Uberlândia- MG, Brazil. The analysis intents to reveal the (inter)relations among the knowledges, the practices and personages (docents) that (re)build, in the daily educational spaces, the scholar Geography(ies) and participate in the formative process of and for citizenship. The method used was inspired in the modality of the oral history thematic. From the oral narratives, reproduced in writen words, of a five Geography teachers group from the municipal education system, we produced a reflection about the construction process of identity and docents knowledges, about the (re)construction manners of geographics knowledges in the scholar context of final grades in Fundamental School. And also about the mediations among different knowledges, personages and practices, in the formation of/for citizenship. The study reveals that in the Geography teaching-learning process the teacher (re)build, permanently, his professional identity, his differents knowledges, his experiences and his dreams. Conclude if a significant and (trans)formative scholar education, demands a critic reflection about the internal position of the educational process, about the initial and continued of the Geography docents, about the curriculums ant the teaching practices and about the production and mobilization of new geographics knowledges in the scholar space/time.